Analisis Kinerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kabupaten Lampung Barat - Ahmad Putra Utama; Ida Hayu Dwimawanti; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
In the measurement against the performance is an important factor to improve the employee performance. The parts which show the ability of employees less maximum can be identified so that can be determined strategy to improve its performance. This research will analyze the performance of which was carried out by employees of Dinas Kependudukan dan Pencatatan Sipil Lampung Barat and the factors that supports and hinder performance of Dinas Kependudukan dan Pencatatan Sipil Lampung Barat. This study using the theory of performance by five dimensions the performance of the results of which is the quantity, the quality of the outcome , punctuality , the presence of, and the ability of work together.The theory of a barrier and supporter of the performance seen from work discipline and motivation work. Data collection techniques used through observation, interview, and documentation with informants employees of Dinas Kependudukan dan Pencatatan Sipil Lampung Barat The result showed the performance of employees conducted by Dinas Kependudukan dan Pencatatan Sipil Lampung Barat still not good because it is still found an obstacle such as the presence of which not enough coming late to the office to quality of work are deficient.While the support the employee performance of Dinas Kependudukan dan Pencatatan Sipil Lampung Barat were the relationship between friends and a superior have been running well and status employees do not things go wrong. In overcoming obstacles there are some suggestions that can be done as improve the quality of human resources, procurement of the finger print of, give strict punishment, proposed the additional budget in accordance with needs that is required in the district budget lampung west.